2022
DOI: 10.1155/2022/1534596
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Recognition and Repair System of Mural Image Cracks Based on Cloud Edge Computing and Digitization

Abstract: Mural painting is the art on the wall, it is the painting that people draw on the wall, it is one of the earliest forms of painting in human history, and it is also an accessory part of the building. The decorative and beautifying functions of murals make them an important aspect of environmental art. Cloud edge computing is a combination of cloud computing and edge computing, that fully absorbs the advantages of both cloud computing and edge computing and maximizes their advantages. In this study, based on cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Therefore, virtual restoration of the murals may have great potential for mural conservation and research [ 17 , 135 ]. Using computer technology, digitally repaired damaged murals can be helpful for the virtual display of the murals, and it has been shown that cloud edge computing could be a useful tool to automatically identify and repair the cracks of murals [ 136 ]. Deep learning and visual reality technology can build a digital recognition model which can accurately identify the colors and drawing materials of each specific color and thus be of great significance for the preservation simulation of murals [ 137 , 138 ].…”
Section: Measures For Mural Restoration and Protectionmentioning
confidence: 99%
“…Therefore, virtual restoration of the murals may have great potential for mural conservation and research [ 17 , 135 ]. Using computer technology, digitally repaired damaged murals can be helpful for the virtual display of the murals, and it has been shown that cloud edge computing could be a useful tool to automatically identify and repair the cracks of murals [ 136 ]. Deep learning and visual reality technology can build a digital recognition model which can accurately identify the colors and drawing materials of each specific color and thus be of great significance for the preservation simulation of murals [ 137 , 138 ].…”
Section: Measures For Mural Restoration and Protectionmentioning
confidence: 99%
“…Intangible cultural heritage should be adapted to digitization in the new era, pay attention to the important role of digitization in the collection, storage, processing, display and dissemination of intangible heritage, and form a renewable digital form, so as to revitalize the vernacular culture in the context of modernity [7]. Based on this, in order to better protect and inherit folk art, and give full play to its unique cultural value and social function in the context of the new era, it is necessary to discuss in depth the development of the digital protection of folk art, the principle of the requirements and the development path, so as to break through the limitations of the development of folk art and other vernacular cultures, and to provide ideas for the promotion of digital protection of China's intangible cultural heritage and the revitalization of the countryside and other related issues [8].…”
Section: Introductionmentioning
confidence: 99%